Political Prioritization of Early Childhood Education during the COVID-19 Pandemic : A Comparative Policy Analysis of Low- and Middle-Income Countries - Neuman, Michelle J. (World Bank, Washington, DC, 2021)
Despite strong evidence of its importance to the welfare of children and societies, early childhood education has been comparatively neglected as a policy priority both before and during the COVID-19 pandemic. This paper seeks to understand what factors have contributed to the lack of priority for early childhood education in distance learning and school reopening plans, by applying a political prioritization framework to the pandemic context in four low- and middle-income countries: Ethiopia, Jamaica, Liberia, and Pakistan. Some aspects of the pre-COVID-19 status quo, which disfavored early childhood education, have continued, including a lack of cohesive support from civil society and a greater focus by international partners on norm promotion and technical assistance than financing. In other respects, the pandemic put early childhood education at an even greater disadvantage. These include perceptions that early childhood education is less suited to distance delivery than other levels of education, concerns about young children’s ability to comply with health protocols, and competition with high-stakes examinations for education ministries’ attention. Previous country experience with pandemics (in Liberia) and a strong coordinating entity (in Jamaica) were mitigating factors. These results point to an urgent need to elevate priority for early childhood education in normal times and improve the resilience of early childhood education in future crises.